2011
DOI: 10.1016/j.vetpar.2010.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the antibody response in birds following infection with wild-type and attenuated strains of Eimeria tenella and Eimeria necatrix

Abstract: Live vaccines containing attenuated parasite strains are increasingly used to control chicken coccidiosis. In this paper antibody responses elicited by infections with wild-type and attenuated strains of Eimeria tenella and Eimeria necatrix were characterized by immunoblotting and ELISA with homologous and heterologous antisera. Few differences between antisera from birds infected with wild and attenuated strains of E. tenella were evident in immunoblots conducted with merozoite antigen preparations from both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
(23 reference statements)
1
6
0
Order By: Relevance
“…In order to design an effective genetically engineered vaccine, the most promising antigens were derived from the early endogenous stages of the Eimeria life cycle (sporozoites and merozoites). This correlates with the findings observed in naturally infected chickens, where these stages induce the strongest anti- Eimeria immunity [ 8 , 45 , 47 , 48 , 49 ]. Many of these antigens have critical roles in host–parasite interactions [ 3 , 5 , 14 , 16 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In order to design an effective genetically engineered vaccine, the most promising antigens were derived from the early endogenous stages of the Eimeria life cycle (sporozoites and merozoites). This correlates with the findings observed in naturally infected chickens, where these stages induce the strongest anti- Eimeria immunity [ 8 , 45 , 47 , 48 , 49 ]. Many of these antigens have critical roles in host–parasite interactions [ 3 , 5 , 14 , 16 ].…”
Section: Discussionsupporting
confidence: 89%
“…Western blot analysis allowed us to identify some antigenic differences between the sporozoites and merozoites, although the majority of the antigens seemed to be common between them. The sharing of antigens between sporozoites and merozoites has been demonstrated previously in studies with chicken and rabbit antisera [ 45 , 47 , 48 , 49 ]. As a matter of fact, most antigens with a molecular weight higher than 50 kDa seemed to be shared by these two life cycle stages [ 45 , 49 ].…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Immunized with r Em GAM56 and r Em ROP17 could induce humoral immunity in the rabbits, and the specific IgG was significantly increased. Recent research has proven that antibodies are involved in the occurrence of Eimeria infection ( 60 , 61 ), where antigen-specific antibodies inhibited adhesion to host cells ( 62 ). Moreover, it was shown that there was an excellent correlation between antibody titer and protection ( 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…Live attenuated parasite vaccines induce pronounced immune responses (Constantinoiu et al 2011) and are used to control outbreaks of infection in the field (Chapman et al 2002). Furthermore, live oocyst vaccines proved to be useful to restore ionophore sensitivity in poultry operations that contain an ionophore-resistant population of Eimeria oocysts (Jenkins et al 2010).…”
Section: Introductionmentioning
confidence: 99%